Porphyrins in troubled times: a spotlight on porphyrins and their metal complexes for explosives testing and CBRN defense. (26th January 2018) - Kielmann, Marc; Prior, Caroline; Senge, Mathias O.
Abstract : A critical perspective on (metallo)porphyrins in security-related applications: the past, present and future of explosives detection, CBRN defense, and beyond. Abstract : Porphyrins are large π-aromatic systems that can complex metal ions from all across the periodic table. The resulting metalloporphyrins are readily tunable with regards to analyte detection properties, and constitute an important class of chemical sensors. In light of the current geopolitical situation and security concerns, we review the potential of porphyrins and their metal complexes for the detection of explosives and their use in chemical, biological, radiological and nuclear (CBRN) defense and set them in the context of up-and-coming security-related applications.